Pengaruh Tekanan Waktu, Tindakan Supervisi, Locus of Control, dan Resiko Audit Terhadap Penghentian Prematur Prosedur Audit di BPKP Sumut - Maulana Idham S Nasution; Wilisra Wilfrida Marbun; Munawarah Munawarah (Ekonomi, Keuangan, Investasi dan Syariah (EKUITAS), 2020)
This study aims to determine the impact of time pressure, super vision actions, locus of control and audit risk on premature termination of audit procedures. Data collection techniques in this study used a questionnaire (questionnaire). The sample collection technique used is the nonprobability sampling method. The types of data in this study are primary and secondary data. The results showed that time pressure, supervision measures, locus of control and audit risk simultaneously had a positive and significant effect on premature termination of audit procedures at BPKP in Medan. Partially time pressure has no positive and insignificant effect on Premature Termination of Audit Procedures at BPKP in Medan. Partially, the supervision action has a positive and significant effect on the Premature Termination of Audit Procedures at BPKP in Medan. Partially Locus of Control has a positive and significant effect on Premature Termination of Audit Procedures at BPKP in Medan. Partially audit risk does not have a positive and significant effect on Premature Termination of Audit Procedures at BPKP in Medan